DEMOCRACY AND GOVERNMENT SPENDING : IS THERE A LINK? - Shalihah, Haya Farras; Febriani, Ratu Eva (LPPM STIE Muhammadiah Bandung, 2023)
Government spending is included in the fiscal policy component, namely the steps taken by the government to control economic development by determining the amount of government income and spending each year. This research aims to assess the influence of Democracy, PAD, Balancing Funds and GRDP on government spending in Indonesia in 2017-2021. The data type used is secondary data from the Central Statistics Agency and the Indonesian Ministry of Finance. The analytical method used in this research is panel data regression analysis with Eviews 12 software. The results of this research find that Democracy has no impact on the allocation of government spending. In contrast, PAD, Balancing Funds and GRDP positively and significantly affect government spending in Indonesia. Government spending is included in the fiscal policy component, namely the steps taken by the government to control economic development by determining the amount of government income and spending each year. This research aims to assess the influence of Democracy, PAD, Balancing Funds and GRDP on government spending in Indonesia in 2017-2021. The data type used is secondary data from the Central Statistics Agency and the Indonesian Ministry of Finance. The analytical method used in this research is panel data regression analysis with Eviews 12 software. The results of this research find that Democracy has no impact on the allocation of government spending. In contrast, PAD, Balancing Funds and GRDP positively and significantly affect government spending in Indonesia.